2015
DOI: 10.5424/fs/2015241-06351
|View full text |Cite
|
Sign up to set email alerts
|

High seed dispersal ability of Pinus canariensis in stands of contrasting density inferred from genotypic data

Abstract: Aim of the study: Models that combine parentage analysis from molecular data with spatial information of seeds and seedlings provide a framework to describe and identify the factors involved in seed dispersal and recruitment of forest species. In the present study we used a spatially explicit method (the gene shadow model) in order to assess primary and effective dispersal in Pinus canariensis.Area of study: Pinus canariensis is endemic to the Canary Islands (Spain). Sampling sites were a high density forest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A significant constraint lies in the uncertainty associated with seed dispersal estimation [16,55]. Notably, [38], conducting research in the same stand, proposed a different dispersal model utilizing genetic markers for mother tree identification, while, even in our study there were other alternative models, such as the Gamma, that could have been used for modeling. Furthermore, despite employing an extensive seed monitoring network with 103 seed traps over two study years, the inherent variability in seed set due to masting events [56] and climate conditions [57] introduces uncertainties into the optimal selection of seed-trees.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A significant constraint lies in the uncertainty associated with seed dispersal estimation [16,55]. Notably, [38], conducting research in the same stand, proposed a different dispersal model utilizing genetic markers for mother tree identification, while, even in our study there were other alternative models, such as the Gamma, that could have been used for modeling. Furthermore, despite employing an extensive seed monitoring network with 103 seed traps over two study years, the inherent variability in seed set due to masting events [56] and climate conditions [57] introduces uncertainties into the optimal selection of seed-trees.…”
Section: Discussionmentioning
confidence: 89%
“…27 m. Within the stand, the dominant orientations are south and south-east and the slope varies locally from 0% to 110%, lying predominantly in the 40%-45% range. Understory vegetation is scarce but seedlings of P. canariensis have been recorded in varying densities (see [38] for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, future studies using molecular markers to identify parentage relationships between parents and successfully established offspring may be used to confirm the patterns revealed by inverse modeling ( [37,38]). Previous studies have shown that results for sapling dispersal kernels estimated via classical inverse modeling were remarkably similar to the ones obtained by genetic methods [36,39].…”
Section: Fecundity Dynamicsmentioning
confidence: 99%